VD_FINDINFO HC / 2019 / 546 vom 20. Mai 2019 - VD Tribunal cantonal (2019)
PROCÈS DEVENU SANS OBJET, PREUVE À FUTUR, RÉPARTITION DES FRAIS | 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 106 al. 3 CPC (CH), 107 al. 1 let. a CPC (CH), 107 al. 1 let. b CPC (CH), 107 al. 1 let. c CPC (CH), 107 al. 1 let. e CPC (CH), 107 al. 1 let. f CPC (CH), 107 al. 2 CPC (CH), 241 CPC (CH), 242 CPC (CH), 74 CPC (CH)